2021
DOI: 10.2147/nss.s324142
|View full text |Cite
|
Sign up to set email alerts
|

How our Dreams Changed During the COVID-19 Pandemic: Effects and Correlates of Dream Recall Frequency - a Multinational Study on 19,355 Adults

Abstract: Objective Many have reported odd dreams during the pandemic. Given that dreams are associated with mental health, understanding these changes could provide crucial information about wellbeing during the pandemic. This study explored associations between COVID-19 and dream recall frequency (DRF), and related social, health, and mental health factors. Methods We conducted a cross-sectional web survey of 19,355 individuals in 14 countries from May to July 2020. We collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
95
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(102 citation statements)
references
References 78 publications
7
95
0
Order By: Relevance
“…Other data concerning the whole sample and analyzed with different aims have been reported elsewhere. 13 , 22 , 42…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other data concerning the whole sample and analyzed with different aims have been reported elsewhere. 13 , 22 , 42…”
Section: Methodsmentioning
confidence: 99%
“…The selection of dependent measures was based on (a) the findings of other studies published during pandemic 18–28 and (b) the need to avoid any overlapping (ie, duplication of results) with results of other publications of the ICOSS group. 13 , 22 , 42 The complete protocol is available on Partinen et al 41 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Against this background, a growing number of research papers were showing that the outbreak was associated with relevant psychological symptoms [3,4] and sleep quality was significantly worsened [4][5][6]. Many investigations also explored oneiric activity during the pandemic [7][8][9][10][11][12][13][14][15][16]. Results from different countries revealed higher dream-recall frequency during the pandemic (e.g., [16]).…”
Section: Introductionmentioning
confidence: 99%
“…Many investigations also explored oneiric activity during the pandemic [7][8][9][10][11][12][13][14][15][16]. Results from different countries revealed higher dream-recall frequency during the pandemic (e.g., [16]). Moreover, subjects reported that dream content was pandemic-related [7][8][9]17].…”
Section: Introductionmentioning
confidence: 99%